2017
DOI: 10.1136/sextrans-2016-052977
|View full text |Cite
|
Sign up to set email alerts
|

Using theories of practice to understand HIV-positive persons varied engagement with HIV services: a qualitative study in six Sub-Saharan African countries

Abstract: ObjectivesThis article considers the potential of ‘theories of practice’ for studying and understanding varied (dis)engagement with HIV care and treatment services and begins to unpack the assemblage of elements and practices that shape the nature and duration of individuals’ interactions with HIV services.MethodsWe obtained data from a multicountry qualitative study that explores the use of HIV care and treatment services, with a focus on examining the social organisation of engagement with care as a practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 33 publications
5
60
0
Order By: Relevance
“…Other researchers have also shown that PLHIV often blame themselves for dis-engaging from care, and that this sense of guilt and fault need to be carefully navigated by health care workers as they move forward in their treatment journeys (Layer et al, 2014). In addition, the precarity of the social transformations that accompany regimen change that we observed echo the findings in Russell and Seeley's research in Uganda among individuals who initiated first-line ART following HIV-related illnesses and recall the complexity of achieving sustained engagement with HIV care and treatment in the context of pervasive stigma and challenging social circumstances Skovdal et al, 2017;Stern, Colvin, Schutz, Burton, & Meintjes, 2017;Wamoyi et al, 2017). Other researchers have also noted apparent contradictions or paradoxes in the experiences of patients who have very long treatment histories, whereby optimism and hope often co-exist alongside new challenges that arise from sustained treatment-taking, and which may risk undermining treatment-taking (Nixon et al, 2018).…”
Section: Discussionsupporting
confidence: 62%
“…Other researchers have also shown that PLHIV often blame themselves for dis-engaging from care, and that this sense of guilt and fault need to be carefully navigated by health care workers as they move forward in their treatment journeys (Layer et al, 2014). In addition, the precarity of the social transformations that accompany regimen change that we observed echo the findings in Russell and Seeley's research in Uganda among individuals who initiated first-line ART following HIV-related illnesses and recall the complexity of achieving sustained engagement with HIV care and treatment in the context of pervasive stigma and challenging social circumstances Skovdal et al, 2017;Stern, Colvin, Schutz, Burton, & Meintjes, 2017;Wamoyi et al, 2017). Other researchers have also noted apparent contradictions or paradoxes in the experiences of patients who have very long treatment histories, whereby optimism and hope often co-exist alongside new challenges that arise from sustained treatment-taking, and which may risk undermining treatment-taking (Nixon et al, 2018).…”
Section: Discussionsupporting
confidence: 62%
“…Reasons for discontinuing ART have been typically described as complex . The thematic analysis revealed similar reasons for disengagement from care to those described by Ware et al.…”
Section: Discussionsupporting
confidence: 56%
“…Reasons for discontinuing ART have been typically described as complex [22,23]. The thematic analysis revealed similar reasons for disengagement from care to those described by Ware et al who identified competing social and economic demands, violence, lack of family or community support, and dissatisfaction with care [22].…”
Section: Discussionsupporting
confidence: 54%
“…If our interest is to understand what it takes for people living with HIV to join, maintain or defect from engagement with HIV treatment, we need to understand what and how other life practices, such as care, intersect with this particular practice. This insight can be used to form or break, strengthen or weaken links between them ( Blue et al, 2016 ), with the aim of enhancing engagement with HIV treatment ( Skovdal et al, 2017 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%